Ketahanan Bank Syariah di Indonesia dalam Menghadapi Volatilitas Ekonomi Global 2026 - Nanang Kosim; Moh Syaiful (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
Global economic volatility is characterized by uncertainty in global monetary policy, geopolitical conflicts, commodity price fluctuations, and inflationary pressures, impacting the financial sector, including Islamic banking in Indonesia. This study aims to analyze the resilience of Islamic banks and the factors influencing their ability to adapt to external shocks. This study uses a qualitative approach with a library research method. This approach was chosen because it is relevant to explore concepts, theories, and empirical findings related to this research. The study results indicate that Islamic banks are relatively more resilient due to their asset-based financing model and profit-sharing principles, but still face exchange rate risks, liquidity risks, and pressures on financing quality. Strengthening risk management, product innovation, digitalization, and support from macroprudential policies are key factors in maintaining the stability of the Islamic banking sector in the face of global economic volatility